KEGIATAN ESTRAKULIKULER PENCAK SILAT PAGAR NUSA SATRIA AGUNG DALAM MEMBENTUK PENDIDIKAN AKHLAK SISWA SMK NEGERI 2 SUKOREJO - Jamhuri (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2021)
Today many people are faced with probelematics, especially in the reduction of behavior or attitudes that deviate far from good character. The decline in deviant behavior is triggered by the influence of globalization and promiscuity. Globalization touches various aspects of human life such as economic activities, trade, and culture that are able to shape the character of world civilization that is different from before. The current moral crisis has devastated the values ​​of religious and cultural law and customs. Morals are very important for humans. The urgency of this morality is not only felt by humans in individual life, but also felt in family and community life, even it is also felt in the life of the nation or state. The purpose of this study is to: 1) To find out the implementation of the martial arts fence of the nusa satria agung fence in forming moral education in State Public School 2 Sukorejo. 2) To find out the values ​​of the education of pencak silat fence nusa satria in shaping the moral education in Smk Negeri 2 Sukorejo. 3) To find out what are the strengths and weaknesses of pencak silat in shaping the moral education in Smk Negeri 2 Sukorejo. This research was conducted with a qualitative method through a descriptive approach, because the focus of his research was the implementation of the martial arts fence of the nusa satria agung in shaping the moral education at SMK 2 Sukorejo. The data collection procedure performed is to use the method of observation, documentation and interviews. To analyze the data, researchers used data reduction analysis, data presentation, verification, checking the validity of the data, and triangulation. The results of this study indicate that: 1) the implementation of pencak silat fence nusa satria agung in shaping the moral education is carried out there are six stages including; (a) Opening and praying (b) Greeting fences nusa, (c) Warming up, (d) Material, (e) Art and sparring, (f) closing and praying. 2) The values ​​of pencak silat in the fence of nusa satria in forming moral education (a) Come early and get in the habit of saying greetings (b) discipline and never giving up, (c) relief activities. 3) What are the strengths and weaknesses of pencak silat in shaping moral education including: a) a vehicle for moral education, martial arts, a place for learning organizations. b) lack of competition performance, facilities and infrastructure, lack of concentration of learning.